2000
DOI: 10.1007/s004360050036
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Trichinella spiralis larvae after treatment with the anti-allergic compound ketotifen

Abstract: Ketotifen was used as an anti-allergic agent to study the relationship between eosinophil-related responses and IgG1 and IgG2a antibody responses in BALB/c mice infected with Trichinella spiralis. The results showed that leukocyte and eosinophil numbers and interleukin-5 (IL-5) concentrations in the peritoneal fluid increased after exposure to nematodes and the increases were slightly greater in animals treated with ketotifen. A decreased concentration of eosinophil peroxidase and an elevation in IgG1 accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
3
7
1
Order By: Relevance
“…T. spiralis muscle larvae death was correlated with enhanced IFN-γ and reduced IL-4 production (Kang et al, 2012). Vallance et al (2000) and Doligalska (2000) confirmed that IL-5 is not only essential for the onset of intestinal eosinophilia, but also makes a significant contribution to enteric host defence during challenge T. spiralis infections, what correlated with our results during the intestinal phase after reinfection. IL-5 expression is only minimally protective during a primary T. spiralis infection but may be to protect against repeated exposure to gastrointestinal parasite.…”
Section: Discussionsupporting
confidence: 83%
“…T. spiralis muscle larvae death was correlated with enhanced IFN-γ and reduced IL-4 production (Kang et al, 2012). Vallance et al (2000) and Doligalska (2000) confirmed that IL-5 is not only essential for the onset of intestinal eosinophilia, but also makes a significant contribution to enteric host defence during challenge T. spiralis infections, what correlated with our results during the intestinal phase after reinfection. IL-5 expression is only minimally protective during a primary T. spiralis infection but may be to protect against repeated exposure to gastrointestinal parasite.…”
Section: Discussionsupporting
confidence: 83%
“…The low number of antigens might be bound into immune complexes. Contrary, T. pseudospiralis induced a higher level of specific IgM immunoglobulines during the intestinal phase till (Doligalska, 2000) and newborn larve are more sensitive in vitro to IgG 1 in antibody-dependent cellular cytotoxicity (Moskwa, 1999). The low infective dose of 10 larvae of T. spiralis in our study stimulated IgG 1 antibody production from day 20 p.i., with a significant elevation from day 45 p.i., but T. britovi infection induced the generation of IgG 1 antibodies not until day 60 p.i.…”
Section: Discussioncontrasting
confidence: 63%
“…The protective isotypes IgG 1 and IgG 2 are involved in the inflammatory response. An elevation of IgG 1 accompanies the muscle phase of infection (Doligalska, 2000) and newborn larve are more sensitive in vitro to IgG 1 in antibody-dependent cellular cytotoxicity (Moskwa, 1999). Antibodies significantly participate in Trichinella entrapment and rapid expulsion of infective larvae L1, reduce adult worm fecundity and kill newborn larvae (Appleton & Usack, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine IL-5 indicates the severity of inflammation, because it directly induces degranulation of eosinophils (Horie et al 1996), but it does not increase activity of eosinophils (Kita et al, 1992). Vallance et al (2000) and Doligalska (2000) confirmed that IL-5 is not only essential for the onset of intestinal eosinophilia, but also makes a significant contribution to enteric host defence during challenge T. spiralis infections. IL-5 expression is only minimally protective during a primary T. spiralis infection but may protect against repeated exposure to gastrointestinal parasite, what correlated with our results during the intestinal phase after the heavy infection.…”
Section: Discussionmentioning
confidence: 77%